INVESTIGATION OF FAULT CURRENT LIMITING TRANSFORMER USING VARIABLE REACTANCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
To demonstrate experimentally the capability of a reactive variable impedance transformer to limit the fault current and set a secondary voltage is the goal of this task. This transformer is capable of changing its leakage reactance using a shift of a mobile iron core block. It plays threerole that is voltage transformation, fault current limiting and voltage regulation. A small test device was developed and tested almost these functions. Its features should go ahead and they also explained.